High-resolution observations of NO2 and CO2 emission plumes from EnMAP satellite measurements - Borger, Christian; Beirle, Steffen; Butz, André; Scheidweiler, Leonie Olivia; Wagner, Thomas (Environmental research letters, 2025)
Accurate quantification of emissions from anthropogenic sources is crucial for monitoring greenhouse gases and air pollution. Nitrogen oxides (NOx) and carbon dioxide (CO2) are of particular interest due to their role in atmospheric chemistry and global warming, respectively. Satellite observations are a key component for independent monitoring of emissions on a global scale. In this study, we demonstrate for the first time the simultaneous detection of NO2 and CO2 in power plant plumes from environmental mapping and analysis program satellite measurements with a spatial resolution of a few tens of metres and up to several tens of kilometres downwind. Our results enable us to estimate CO2 and NOx emissions from thermal power plants, study the chemistry of emission plumes and derive NOx/CO2 ratios reflecting power plant characteristics.